Comparative ovarian biometry and oocyte retrieval methods in pig - Biswajit saikia; Soumen Naskar; Yoya vashi; Santanu Banik; Rajendran Thomas; Ajay Kumar Singh; Dilip Kumar Sarma; Sujoy Kumar Dhara (Indian Journal of Veterinary and Animal Sciences Research, 2023)
Biometry and follicular parameters of porcine ovaries sourced from organized and unorganized-slaughterhouses and relative comparison of oocyte retrieval methods, namely aspiration and slicing, are reported in the present study. Average length and width of the ovaries, and numbers of surface and cystic follicles were higher in ovaries sourced from organized slaughterhouses. Average number of oocytes recovered per ovary by slicing (12.93±1.49) was significantly higher (P<0.01) than aspiration (6.36±1.02). However, aspiration yielded higher percentage (65.21±5.71) of good quality oocytes (A) (P<0.01) suitable for upstream applications of assisted reproductive technologies (ART). Further, our study reveals that ovaries sourced from unorganized slaughterhouses can also be used for ART, and use of aspiration method may yield better quality oocytes.